1998
DOI: 10.1097/00004872-199816121-00033
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of pulse wave velocity and augmentation index measured by pulse wave analysis

Abstract: PWA is a simple and reproducible technique with which to measure PWV and AIx. Reproducibility accords with that reported by other workers using different methodologies. PWA may, therefore, be suitable for large-scale population and intervention studies investigating the clinical relevance of vascular stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
638
3
22

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 861 publications
(720 citation statements)
references
References 14 publications
49
638
3
22
Order By: Relevance
“…The correlation between invasive and non-invasive techniques was high for the estimation of central SBP (r ¼ 0.99, Po0.001). 56 As long as reproducibility is regarded, our estimation for the intra-observer difference for the measurement of AI was 1.75 ± 4.6%, which is close to the difference reported in a previous study (0.49 ± 5.37), 21 showing that the method has very good reproducibility.…”
Section: Lydakis Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…The correlation between invasive and non-invasive techniques was high for the estimation of central SBP (r ¼ 0.99, Po0.001). 56 As long as reproducibility is regarded, our estimation for the intra-observer difference for the measurement of AI was 1.75 ± 4.6%, which is close to the difference reported in a previous study (0.49 ± 5.37), 21 showing that the method has very good reproducibility.…”
Section: Lydakis Et Alsupporting
confidence: 88%
“…Pulse wave analysis has previously been described as a simple and reproducible non-invasive method for assessing augmentation index (AI). 21 In brief, a high-fidelity micromanometer (SPC-301) was used to flatten but not occlude the radial artery, using gentle pressure. The radial waveform was recorded on a portable computer.…”
Section: Pulse Wave Analysismentioning
confidence: 99%
“…7,10 The PWV measurement was also shown to have good reproducibility. 12 Venous blood samples were drawn in fasting state, and frozen serum samples stored at -80 degrees were used for biochemical laboratory analyses in the series. 25 …”
Section: Examinations and Materialsmentioning
confidence: 99%
“…18 Moreover, by gating measurements to the R wave of an ECG, and making recordings at two sites, PWV can also be measured. We have already shown that the system can be used reproducibly in various patient groups, 24 and believe that it provides an ideal tool with which to assess arterial stiffness easily and rapidly in large outcome-based studies. 25 PWA may also improve our understanding of the physiological mechanisms regulating arterial stiffness and be a useful method with which to assess the effect of drugs on the arterial tree.…”
Section: Pulse Wave Analysismentioning
confidence: 99%